Preoperative bathing with chloroxylenol versus non-medicated soap in preventing surgical site infection following inguinal herniorrhaphy: A randomized controlled trial to prevent surgical site infection - Oghenevwegba, Akpoghor; Odionyeme, Ugochukwu Richard; Ikponmwosa, Agbonrofo Peter; Omorodion, Irowa (Journal of Surgery and Medicine, 2025)
Background/Aim: Surgical site infections (SSIs) remain prevalent in low- and middle-income countries, exceeding 2% even in clean procedures like elective inguinal herniorrhaphy. While preoperative bathing prevents SSIs, meta-analyses show no advantage of chlorhexidine over non-medicated soap. No studies have compared chloroxylenol soap with non-medicated soap. Methods: We conducted a prospective randomized study of adults undergoing elective open inguinal herniorrhaphy using the Bassini technique under subarachnoid block. Patients bathed 1 h preoperatively with either chloroxylenol soap (Dettol®) or non-medicated soap (Lux®). We monitored wounds for 30 days using CDC infection criteria and analyzed data using IBM SPSS V 22.0. Results: The study included 76 patients (93.42% male) with a mean age of 51.72 (18.70) years. The mean operative time was 49.58 (20.06) min. Right-sided hernias comprised 65.79% of cases, with 81.58% being indirect. SSI incidence was 2.63% (one patient per group), showing no significant difference between chloroxylenol and non-medicated soap (P=1.000). Conclusion: Chloroxylenol soap offers no advantage over non-medicated soap in preventing SSIs after elective inguinal herniorrhaphy.